Analytical BER Performance Evaluation in SISO and MIMO Environments with SC-FDE Modulations and IB-DFE Receivers - Dinis, Rui (2017)
This paper presents the analysis of the obtainment of the theoretical bit error rate (BER) performance in single-input–single-output and multiple-input–multiple-output systems with single-carrier with frequency-domain equalization modulations and iterative receivers based on the iterative block decision feedback equalization concept. Through the consideration of a Gaussian-based approach to obtain the BER performance, we present a simple and accurate model to improve such method by compensating the difference between the theoretical performance results and the ones obtained by simulation.